Extraction of oil from flaxseed using three phase partitioning techniques - Rizvi, Qurat ul Eain Hyder; Sharma, Vasudha; Shams, Rafeeya; Dar, Aamir Hussain; Jan, Bisma; Manzoor, Arshied (Journal of Postharvest Technology, 2021)
Flaxseed used for the extraction of oil has various health benefits as the risks of various chronic diseases are reduced. Flaxseed oil has  gained a great importance because of its edible oil which is considered to contain fantastic source of omega-3 fatty acid Alpha Linolenic  Acid, proteins, lignans, minerals, vitamins etc. Because of its omega-3 fatty acid content it is used to reduce the risk of various heart  diseases. Three-phase partitioning is an efficient bio separation method used for oil extraction from flaxseeds. In this process three  phases are formed. These phases are organic phase, intermediate and aqueous phase. In the top layer solvent is present in  intermediate layer protein and slurry is present and in lower aqueous phase water is present. In tpp, centrifugation for 15 min at 3000  rpm was done to obtain three phases then upper phase is transferred to the flask for Rota evaporation to remove the solvent and get the  oil percentage. Different parameters were optimized to get the higher percentage of oil such as ammonium sulphate, t-butanol, and  petroleum ether, solvent to slurry ratio and protease enzyme. The maximum percentage of oil was obtained at 40 % ammonium  sulphate, t-butanol & petroleum ether ratio to slurry ratio (1:1).
Keywords: Flaxseed oil; three phase partitioning; alpha linolenic acid; chronic diseases; lignans